(untitled) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2024)
According to Shivnath Shastri, the period from 1856 A.D to 1861 A.D was an auspicious time for Bengal. During this time, the widow marriage revolution, Indian Mutiny, Indigo Movement, the demise of Ishwar Chandra Gupta, and the appearance of Madhusudan, among other incidents, occurred. During this period, a drastic change occurred in socio-cultural, political, literary, religious, nationalist, and all aspects of society. The Thakurbari of Jorasanko was the central point of these activities, and it was during this crucial time that Rabindranath was born. In the 19th century, socio-religious reform movements, literary revolutions, and national movements took place. The pioneers of these three movements, such as Devendranath Thakur, Keshav Chandra Sen, Bankim Chandra Chattopadhyay, and Madhusudan Dutta, have been clearly described in this essay based on Rabindranath Tagore’s memoirs, letters, and many other writings. In addition to this, Rabindranath Tagore’s opinions on other elite individuals of different backgrounds have also been described here.